Reconciliation and Implacability in Narratives of Survivors After the War in Bosnia and Herzegovina - Bašić, Goran (Kriminalističke teme, 2015)
Reason(s) for writing and research problem(s): Previous research on post-war society emphasized structural violence with subsequent reconciliation processes. Aims of the paper (scientific and/or social): Researchers have focused on the importance of narratives, but they have neither highlighted narratives about reconciliation nor analyzed conditions for reconciliation in post-war interviews. One aim of the article is analyzing markers for reconciliation and implacability, the second is describing conditions for reconciliation which are actualized in those stories. Methodology/Design: This article analyzes retold experiences of 27 survivors from the war in Bosnia and Herzegovina between 1992 and 1995. The material for the study was gathered through qualitative interviews with 27 individuals who survived the war in north-western Bosnia and Herzegovina. Research/paper limitations: Interactive dynamics which prevailed during the war associate post-war reconciliation with the war time. Results/Findings: These stories of reconciliation, implacability and conditions for reconciliation, are not created in relation to the war as a whole only but also in relation to one’s own and other’s personal actions during the war. General conclusion: These stories on reconciliation become a forum for confrontation between us and them – not least through dissociation from others war actions. In the interviewees stories implacability is predominant however reconciliation is said to be possible if certain conditions are met. These conditions are, among others, justice for war victims, that the perpetrators’ recognize their crimes and display strong emotions (for example remorse and shame).